A dyadic approach to stress and prenatal depression in first‐time parents: The mediating role of marital satisfaction. (3rd March 2021) - Mangialavori, Sonia; Cacioppo, Marco; Terrone, Grazia; O'Hara, Michael W.
Abstract: In the field of perinatal clinical psychology, most studies focus on mothers' psychological states during pregnancy, neglecting the role of their partners. This study used an Actor‐Partner Interdependence Mediation Model to evaluate the mediating role of dyadic satisfaction on the relationship between perceived stress and prenatal depressive symptomatology in both members of male‐female‐mixed‐gender couples who were expecting their first child. One hundred thirty‐eight couples in their third trimester of pregnancy were asked to complete questionnaires about perceived stress, dyadic adjustment, and depression. The model revealed that there was an intrapersonal indirect effect of fathers' perceived stress on prenatal paternal depression through their marital satisfaction. Moreover, an interpersonal indirect effect was found with mothers' perceived stress being associated with prenatal paternal depression through fathers' dyadic satisfaction. Maternal indirect effects were all non‐significant, suggesting that their dyadic satisfaction and that of their partner did not mediate the relation between their perceived stress and that of their partner and their prenatal depression. Findings support the importance of assessing the dyadic satisfaction of couples during pregnancy, especially in expectant fathers, and targeting it in the psychological support offered to couples as a way of improving their prenatal distress, and consequently, their mental health.